Assembly of cellulose nanocrystals in a levitating drop probed by time-resolved small angle X-ray scattering. Issue 38 (21st September 2018) - Liu, Yingxin; Agthe, Michael; Salajková, Michaela; Gordeyeva, Korneliya; Guccini, Valentina; Fall, Andreas; Salazar-Alvarez, Germán; Schütz, Christina; Bergström, Lennart
Abstract : The nanoscale assembly of cellulose nanocrystals from 1 vol% up to 38 vol% is investigated by in situ small angle X-ray scattering. Abstract : Assembly of bio-based nano-sized particles into complex architectures and morphologies is an area of fundamental interest and technical importance. We have investigated the assembly of sulfonated cellulose nanocrystals (CNC) dispersed in a shrinking levitating aqueous drop using time-resolved small angle X-ray scattering (SAXS). Analysis of the scaling of the particle separation distance ( d ) with particle concentration ( c ) was used to follow the transition of CNC dispersions from an isotropic state at 1–2 vol% to a compressed nematic state at particle concentrations above 30 vol%. Comparison with SAXS measurements on CNC dispersions at near equilibrium conditions shows that evaporation-induced assembly of CNC in large levitating drops is comparable to bulk systems. Colloidal states with d vs. c scalings intermediate between isotropic dispersions and unidirectional compression of the nematic structure could be related to the biphasic region and gelation of CNC. Nanoscale structural information of CNC assembly up to very high particle concentrations can help to fabricate nanocellulose-based materials by evaporative methods.